Are digital financial payments constrained by the country’s income? Evidence from the Global Findex database - Marija Antonijević; Isidora Ljumović; Velimir Lukić (Anali Ekonomskog fakulteta u Subotici, 2021)
The combined effect of ICT improvement, digitalization and change in clients’ habits lead to changes in the financial sector worldwide. Increased use of digital financial services (DFS) is a change that might help to increase financial inclusion, which is particularly important for developing countries. As income is considered a critical driver of digital payments, this study aims to determine whether there is a linear relationship between a country's income measured by the level of Gross National Income per capita (GNI p.c.) and the use of digital payment services, i.e., making and receiving digital payments. We used data from the Global Findex and World Bank databases for 2017 to conduct the research, which covered 141 countries. The presence of a linear relationship between the level of GNI p.c. and the use of digital payments was tested using correlation analysis. The results of the correlation analysis show that there is a significant strong positive linear relationship between the level of GNI p.c. and the use of digital payment services in both segments, i.e., making and receiving payments. Findings are consistent with previous research and confirmed the important role of income as a driver of the use of DFS.